Study on photoperiodic modulation of the female fertility of Drosophila biarmipes - Shamim, Ahmed Malik; Sayed, Zarin Sana (Environmental and Experimental Biology, 2023)
Various attributes of light, including the intensity, spectral composition and duration of the photophase, have been documented to have remarkable influence on all aspects of behaviour and physiology of eukaryotic experimental models. This hypothesis was investigated in the present study wherein the effects of photoperiod varying from 6 to 18 h of 24‑h light-dark (LD) cycles was examined on the lifetime fertility (i.e., the viable F1 progeny) of females of the Indian fruit fly, Drosophila biarmipes. The flies were subjected to six types of 24‑h LD cycles (light at 150 lux and dark at 0 lux in all LD cycles) in which the photoperiod varied from extremely short (6 h) to extremely long (18 h) duration. The female fertility was the highest in photoperiods of 10, 12 and 14 h, moderate in 8 and 16 h and the lowest in 6 and 18 h. These results indicate that the performance of the circadian system is at its optimum when it is maintained in zeitgeber cycles wherein the photoperiod is close to that of the natural day of the tropical or sub-tropical region from where the given species or strain originated. This study has great implication in predicting the insect abundance at a particular season of the year when the photoperiod is conducible for optimum reproduction. Such premonition should help the local administrative bodies to take appropriate control measures against the given insect pest and vector insects.